PENERAPAN ALGORITMA BINARY SEARCH PADA APLIKASI E-ORDER - Toyib, Rozali; Darnita, Yulia; Deva, Alba Ragil Sutra (UNIVED Press, 2021)
In the PVJ Restaurant/Cafe business in Bengkulu City, the practice of ordering food and drinks still uses the manual method, where the waiter approaches the visitor and records the order on a piece of paper which is then handed over to the kitchen and cashier. This seems ineffective and allows writing errors to occur which result in inappropriate orders, repeated orders (redundancies), dull pencils, pens or paper orders running out which cuts down on a lot of time to replace them. In addition, with a manual ordering process like this, errors often occur in the ordering sequence due to a backlog of order receipts, this has a negative impact on customer satisfaction. Therefore, a strategy is needed that can simplify the ordering process. Searching is a job that is often done in everyday life. The place to search for data is by tracing the data, the place to search for data can be an array in memory (internal search). The test results are that this application cannot communicate or chat between the user and the Paris Van Java restaurant/cafe in Bengkulu City. The advantage of the Binary Search Algorithm is that it is efficient and faster when searching for a value in a large amount of data, because the data has been sorted first. first and the complexity of the algorithm is smaller, the first disadvantage of Binary Search is that the data must be sorted first so that the search process can run well and is more complicated